2004
DOI: 10.1620/tjem.204.299
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic Drugs Can Change the Composition of Rat Brain Lipids

Abstract: Hypolipidemic drugs are potent serum cholesterol lowering agents used for prevention of coronary heart disease. In addition to their cholesterol lowering effect, these drugs exhibit both pleiotropic beneficial and various neurological side effects. Therefore, we analysed effect of the hypolipidemic drugs, fenofibrate and statins, on membrane lipid composition in the rat brain tissue. Male Wistar rats were given 0.1 mg of fenofibrate, lovastatin, pravastatin, fluvastatin or placebo (control) once daily for six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
(44 reference statements)
2
14
0
Order By: Relevance
“…Effects of fluvastatin in the rat brain were shown by Vecka et al (2004). Another study reported that lovastatin and simvastatin strongly reduced the levels of free cholesterol in synaptozomal plazma membranes and lovastatin and pravastatin significantly reduced cholesterol levels in the exofacial membrane leaflet.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Effects of fluvastatin in the rat brain were shown by Vecka et al (2004). Another study reported that lovastatin and simvastatin strongly reduced the levels of free cholesterol in synaptozomal plazma membranes and lovastatin and pravastatin significantly reduced cholesterol levels in the exofacial membrane leaflet.…”
Section: Discussionmentioning
confidence: 97%
“…The effects of several statins on lipid composition of the brain in rats, including fluvastatin, were observed by Vecka et al (2004), in which fluvastatin, an important member of the statin family, was shown to increase sphingomyelin and to decrease diphosphatidylglycerol contents in rat brains. Yet, the most important changes in the fatty acid profile being in the ceramide monohexosides, lead to a decrease in the content of saturated fatty acids and an increase in the content of polyunsaturated fatty acids.…”
mentioning
confidence: 99%
“…Cholesterol is a principal component of myelin, a fatty sheath that serves an essential role in cellular signaling and blood-brain barrier integrity [7]. Statins, regardless of their lipophilicity and ability to penetrate the blood-brain barrier, alter the composition of brain lipids in rat models [8]. Additionally, reduced serum cholesterol may also enhance blood-barrier permeability, exposing the CNS to normally barred toxins [9].…”
Section: Why It Is Biologically Plausible Thatmentioning
confidence: 99%
“…Glial cells use HMG-CoAR as the rate limiting enzyme in the synthesis of cholesterol (Snipes and Suter 1997). Vecka et al (2004) reported that fenofibrate, fluvastatin, lovastatin and pravastatin alter the brain lipid composition in rats. Simvastatin has also been shown to reduce brain cholesterol synthesis in guinea pigs (Lutjohann et al 2004).…”
Section: Daily Activity Testmentioning
confidence: 99%